2013
DOI: 10.1001/jamaoto.2013.3210
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Activating <emph type="ital">PIK3CA</emph> Mutations in Human Papillomavirus–Positive Oropharyngeal Cancer<alt-title><emph type="ital">PIK3CA</emph> in HPV+ Oropharyngeal Squamous Cell Carcinoma</alt-title>

Abstract: Although there has been a suggestion that activating PIK3CA mutations are common in HPV-positive HNSCC, to our knowledge, this is the first study to clearly identify this phenomenon. Targeting PIK3CA with molecular agents in HPV-positive patients may be a mechanism to improve cure rates and decrease treatment toxic effects in this rapidly growing cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…For example, 38% of squamous cell carcinomas of the cervix and 25% of adenocarcinomas of the cervix have a PIK3CA mutation,[12] but we found that only 18% of small cell carcinomas had this mutation. Mutations in PIK3CA are also commonly found in other HPV-associated malignancies, such as oropharyngeal cancer (28%)[13] and squamous cell anal cancer (22%). [14]…”
Section: Discussionmentioning
confidence: 99%
“…For example, 38% of squamous cell carcinomas of the cervix and 25% of adenocarcinomas of the cervix have a PIK3CA mutation,[12] but we found that only 18% of small cell carcinomas had this mutation. Mutations in PIK3CA are also commonly found in other HPV-associated malignancies, such as oropharyngeal cancer (28%)[13] and squamous cell anal cancer (22%). [14]…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the use of a cotargeting therapeutic strategy using cetuximab and PI3K or mTOR inhibitors as a first line of treatment may instead be ideal. In addition, human papillomavirus (HPV)–positive HNSCCs frequently harbor activating PIK3CA mutations (39,59,60) and exhibit aberrant mTOR activity (23), suggesting that this combined targeted therapy might be also useful in at least a subset of HPV-associated HNSCCs. Overall, we can conclude that the evaluation of mutations in genes encoding RAS and PIK3CA and/or other genetic and epigenetic alterations affecting the activity of the PI3K/AKT/mTOR pathway may predict the potential intrinsic resistance to cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting data sets included 431 HPV-negative and 67 HPV-positive primary HNSCC samples with DNA mutation data and survival information for all but 1 of the HPV-negative HNSCC cases. Patients were stratified as never smokers or heavy smokers (>20 pack year history) based on similar research in the literature (18)(19)(20). Patients with between 1 and 20 pack years (n = 59), patients with no smoking history information (n = 10), and patients who were identified as current or former smokers but lacked pack year history information (n = 90) were excluded.…”
Section: Methodsmentioning
confidence: 99%